Studying University-Industry Collaboration in Latin America: A Systematic Review of the period 1993-2022 - Malena Méndez-Isla; Mariana Versino; Sebastián Varela (Multidisciplinary Journal for Education, Social and Technological Sciences)
This article offers a comprehensive examination of perspectives on university-industry interactions in Latin America. Distinguishing itself from international reviews, the study employs a systematic review of 274 articles across Scopus, Scielo, and Dialnet databases. The research addresses the temporal evolution, disciplinary fields, conceptual approaches, methods, and prevailing topics in the region. Findings reveal a focus on management, economics, business, social sciences, and engineering disciplines. Qualitative methods dominate, while theoretical-conceptual approaches encompass meso-institutional and micro-interactional levels. Key research themes include collaboration results, knowledge transfer, innovation, technological transfer, and collaboration barriers.